The Functional Performance of the BrainPort V100 Device in Persons who Are Profoundly Blind. (March 2016) - Grant, Patricia; Spencer, Lindsey; Arnoldussen, Aimee; Hogle, Rich; Nau, Amy; Szlyk, Janet; Nussdorf, Jonathan; Fletcher, Donald C.; Gordon, Keith; Seiple, William
Introduction: This study was conducted to evaluate the functional performance of the BrainPort V100 device, an FDA-cleared sensory-substitution system, in persons who are profoundly blind (that is, have some or no light perception). Methods: This was a prospective, single-arm, multicenter clinical investigation. Participants received 10 hours of device training and were required to use the device in their everyday environments for 1 year. Functional performance measures of object identification, orientation and mobility (O&M), and word identification were assessed at baseline, in post-device training, and at the 3-, 6-, 9-, and 12-month time points. Results: Fifty-seven participants completed the study and used the device for 1 year. No device-related serious adverse events were reported, demonstrating that the risks associated with the BrainPort are minimal. Participants performed object recognition (91.2% success rate) and O&M (57.9% success rate) tasks beyond chance level. Discussion: This study demonstrates that the BrainPort can be used safely and independently by persons who are blind. Participants with profound blindness can accomplish a set of tasks more successfully by using the BrainPort than without the device. Following initial training, performance on these tasks was maintained or improved over the course of 1 year. Implications for practitioners: The BrainPort is a noninvasive and nonsurgical device that heightens functional independence for persons who are blind. The device presents users with more information about their environment than conventional assistive devices, and can enhance independence in performing activities of daily living.